NILAI EKONOMI EKOSISTEM MANGROVE BERDASARKAN BUKAN NILAI PAKAI DI KELURAHAN KARIANGAU KECAMATAN BALIKPAPAN BARAT KOTA BALIKPAPAN - Jaharudin; Nurul Ovia Oktawati; Erwan Sulistianto (Jurnal Pembangunan Perikanan dan Agribisnis, 2014)
The objectives of this research was to analyse econimic value from option, axistance and bequest value of mangrove ecosystem at Kariangau Sub District West Balikpapan District Balikpapan City. By using Purposive Sampling method which is the result of taking was to interview collect sample from 40 respondents lived and use mangrove ecosystem.The result shown that community of Karianagu Village still has a high consern on the availability of mangrove ecosystem. mangrove ecosystem economic value consisting of option, existance, and bequest value were Rp.12.702.012.285,00 per year, means if there is damage to the mangrove ecosystem the loss is to be received by Rp12.702.012.285,00 per year, from total mangrove ecosystem area ± 2.037 Ha or Rp.6.235.646,00 per hectare per year.